Perception of Climate Change Adaptation in Black Agricultural Communities of Santa Cecilia, Risaralda, Colombia - Quinto Mosquera, Omar; Amaya Castaño, Gloria Clemencia (Sociedad y Economía, 2025)
Introduction Climate change affects agricultural production systems by altering rainfall patterns. In rural areas of Colombia, increased rainfall and temperature cause damage to crops due to water stress, and the arrival of pests and diseases. In this collective territory, agriculture is the basis of subsistence and ancestral activity where communities adapt to environmental conditions through spontaneous practices. Objective The purpose of this work was to understand farmers’ perception of climate change, in relation to the impact on agriculture and ancestral practices of the Black communities of Santa Cecilia, municipality of Pueblo Rico, Risaralda, period 1991-2021. Methodology The methodology was qualitative descriptive. Twenty-six interviews were carried out with farmers, and with different agro-productive associations in the collective territory. Results The results indicated that through Law 70 of 1993, community councils were created in the national territory, recognizing ethnic and cultural communities; as well as their association and participation in decision-making to counteract the impact of climate change on agriculture and its solidarity economy. Conclusions Among the conclusions, we can say that the links between communities and the natural environment have allowed the adaptation of crops with practices that favor biodiversity, such as the diversification of crops on the same land together with native herbaceous and forest species, and the use of extracts based on native plants for phytosanitary control.